The Relationship Of Waterfood Conditions And The Incident Of Malaria In Waimaringi Village, Kodi Balaghar District, District, Southwest Sumba, East Nusa Tenggara - Suhardin Musa Ibrahim; Ukik Agustina; Setyo Budi Susanto (Universitas STRADA Indonesia, 2024)
Malaria is a health problem that can cause death . The high incidence of malaria is closely related to several factors . Such as during the rainy season where spring water flows stagnant, in puddles of rainwater on the ground, and in rock holes. In the dry season, groundwater sources decrease, causing puddles to form along rivers. These puddles of water are used as breeding places. The aim of the research is to determine the relationship between standing water conditions and the incidence of malaria in Waimaringi Village . The type of research used is analytical observational with a cross-sectional approach . Population size 800 respondents. The sample was selected using purposive sampling totaling 267 respondents. . Data analysis used bivariate analysis with the Chi Square test at the degree of significance α ≤ 0.05 . The research results were significant is 0.000 or smaller than 0.05, then Ho is rejected and Ha is accepted where there is a relationship between standing water conditions and the incidence of malaria in Waimaringi Village.